Mexico's Evolving Democracy : A Comparative Study of the 2012 Elections - Moreno, Alejandro; Lawson, Chappell H., 1967-; Greene, Kenneth F., 1969-; Domínguez, Jorge I., 1945- (Book collections on Project MUSE., 2015)
"Jorge Dominguez and his colleagues deliver an exceptional analysis of the 2012 Mexican elections through their continuation of the panel studies they ran for the 2000 and 2006 elections. They analyze the elections from both traditional and non-traditional vantage points, seeking fuller answers to the lingering question as to why Mexicans once again elected "la dictadura perfecta" (the perfect dictatorship), referring to the PRI's grip on power for most of the twentieth century. To evaluate the PRI's rehabilitation and eventual electoral success, Dominguez and his team of distinguished political scientists of Mexican electoral politics explore Mexico's electoral institutions, parties, candidates, campaign strategies, public opinion surveys, and media coverage as well as issues of clientelism, corruption, drugs, violence, and the rise of new protest movements in the run-up to and aftermath of the elections. Not only does the book provide rich detail for Latin American electoral and democratization scholars, but its coherent narrative will also appeal to those unfamiliar with Mexican politics. Parts One and Two of the book provide an excellent recap of the "state of play" in 2012; Part Three analyzes why Mexicans voted as they did; and Part Four considers the election's implications for Mexico's political system more broadly. The book will be sought out by scholars and upper level undergraduate and graduate students of comparative politics, democratization studies, and Mexican and Latin American politics. There should also be interest among policymakers"--